Increased Akt-Driven Glycolysis Is the Basis for the Higher Potency of CD137L-DCs - Zeng, Qun; Mallilankaraman, Karthik; Schwarz, Herbert (Frontiers in Immunology, 2019)
CD137 ligand-induced dendritic cells (CD137L-DCs) are a new type of dendritic cells (DCs) that induce strong cytotoxic T cell responses. Investigating the metabolic activity as a potential contributing factor for their potency, we find a significantly higher rate of glycolysis in CD137L-DCs than in granulocyte macrophage colony-stimulating factor and interleukin 4 induced monocyte-derived DCs (moDCs). Using unbiased screening, Akt-mTORC1 activity was found to be significantly higher throughout the differentiation and maturation of CD137L-DCs than that of moDCs. Furthermore, this higher activity of the Akt-mTORC1 pathway is responsible for the significantly higher glycolysis rate in CD137L-DCs than in moDCs. Inhibition of Akt during maturation or inhibition of glycolysis during and after maturation resulted in suppression of inflammatory DCs, with mature CD137L-DCs being the most affected ones. mTORC1, instead, was indispensable for the differentiation of both CD137L-DCs and moDCs. In contrast to its role in supporting lipid synthesis in murine bone marrow-derived DCs, the higher glycolysis rate in CD137L-DCs does not lead to a higher lipid content but rather to an accumulation of succinate and serine. These data demonstrate that the increased Akt-driven glycolysis underlies the higher activity of CD137L-DCs.